Rangelands Atlas - International Livestock Research Institute; International Union for Conservation of Nature; World Wide Fund for Nature; Food and Agriculture Organization of the United Nations; United Nations Environment Programme; International Land Coalition (International Livestock Research Institute, 2021)
Rangelands can be described as land on which the vegetation is predominantly grasses, grass-like plants, forbs or shrubs, and often with trees that are grazed or have the potential to be grazed by livestock and wildlife. They are diverse in their vegetation driven by highly fluctuating rainfall, temperature and other climate phenomena, and habitat for a wide range of wildlife, many species of which are found nowhere else. Rangelands store vast amounts of carbon and either originate or serve as freshwater catchment areas for most of the world’s largest rivers and wetlands. Rangelands are home to millions of people, from pastoralists to hunter-gatherers to ranchers to conservationists. Rangelands feed millions of people worldwide. Rangelands have significant cultural and aesthetic value too, and for many, are places of inspiration and beauty. This Rangelands Atlas has been developed to document and raise awareness on the enormous environmental, economic and social value of rangelands as well as their different ecosystems. It highlights many of the changes taking place in rangelands due to climate change, land use and conversion trends, investments and other changes: of most concern is the predicted trends of climate change and biodiversity loss, which will have significant impacts on some rangeland ecosystems. The spatial mapping of rangelands was produced by focusing on seven of the 14 global biomes categorised by WWF in their mapping of terrestrial ecoregions around the world. These seven biomes include different types of mainly dryland grasslands, savannas, shrublands and forests, together with wetter and colder biomes such as tundra. Though this mapping does not take into account actual land use and other changes that have taken place on the ground, it is a useful starting point for identifying, documenting and raising awareness on the overall characteristics of rangelands, their contribution to livestock and other food production, ecosystem services, conservation and the broader trends of change taking place. The Atlas also highlights significant data gaps in rangelands, which have seen proportionately less investment in this regard than other land uses and ecosystems. The spatial map of rangelands is combined with other existing global datasets on different themes, to produce a mapping of that data ‘for rangelands.’ Each entry is presented with a short explanation of the map, some key figures produced from the big data that produced the map, a story from the field adding a taste of a local experience and/or perspective, and some explanation of terminologies used in the map as required. We are reliant on the accuracy of the datasets we have accessed: the data have not been verified at regional, country or local level, and therefore is only an indicator of broad and estimated figures and trends.